2018
DOI: 10.1093/cid/ciy574
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Community Treatment With Azithromycin and Ivermectin Mass Drug Administration for Control of Scabies and Impetigo

Abstract: Co-administration of azithromycin with ivermectin led to similar decreases in scabies and impetigo prevalence compared to ivermectin alone. The proportion of impetigo lesions containing pyogenic streptococci declined following MDA. There was a transient increase in the proportion of macrolide-resistant S. aureus strains following azithromycin MDA. Registered on clinicaltrials.gov (NCT02775617).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 31 publications
5
72
0
Order By: Relevance
“…Ten observational studies over two decades in remote northern Australia have found that Australian Aboriginal children have the highest documented prevalence of impetigo worldwide . The median prevalence of impetigo in remote Australian Aboriginal children is 45% (interquartile range [IQR], 34–49%), equating to almost half of all Aboriginal children in remote Australia with impetigo at any one time, while up to one‐third of children will also have scabies (Box 3). Comparatively, the median prevalence of impetigo in Africa (median, 7.0%; IQR, 4.1–12.3%), Asia (median, 7.3%; IQR 3.0–16.1%) and Oceania (median, 29.7%; IQR, 14.7–42.0%) is much lower, but contributes more substantially to the overall burden of children with impetigo at any one time due to larger populations, being in excess of 162 million children .…”
Section: Epidemiology Of Skin Infections In Australian Aboriginal Chimentioning
confidence: 99%
“…Ten observational studies over two decades in remote northern Australia have found that Australian Aboriginal children have the highest documented prevalence of impetigo worldwide . The median prevalence of impetigo in remote Australian Aboriginal children is 45% (interquartile range [IQR], 34–49%), equating to almost half of all Aboriginal children in remote Australia with impetigo at any one time, while up to one‐third of children will also have scabies (Box 3). Comparatively, the median prevalence of impetigo in Africa (median, 7.0%; IQR, 4.1–12.3%), Asia (median, 7.3%; IQR 3.0–16.1%) and Oceania (median, 29.7%; IQR, 14.7–42.0%) is much lower, but contributes more substantially to the overall burden of children with impetigo at any one time due to larger populations, being in excess of 162 million children .…”
Section: Epidemiology Of Skin Infections In Australian Aboriginal Chimentioning
confidence: 99%
“…Almost 900 million doses of azithromycin have been distributed by trachoma control programmes since 1999 42 and in Amhara alone 15 million doses are administered every year. 3 Mass distribution of azithromycin is likely to become more common as more evidence emerges of off-target effects such as reducing infectious diseases, 23,[43][44][45] diarrheal diseases 46 and childhood mortality. 22,[47][48][49][50] There is concern about the impact of these programmes on development of antimicrobial resistance in Ct and other bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…WGS additionally allows monitoring of emergence of antimicrobial resistance alleles in Ct, [17][18][19] which is of critical importance as MDA with azithromycin is key for trachoma control, and is also under consideration as an intervention for childhood mortality, 20,21 neonatal sepsis, 22 and bacterial skin diseases. 23 The Trachoma Control Program in Amhara has conducted multiple studies to better understand the epidemiology of trachoma in communities that have received approximately 5 years of annual MDA with azithromycin, yet still have significant levels of Ct infection and trachomatous disease. The resolution of WGS allows for a greater understanding of Ct transmission patterns, presence of putative virulence determinants, and identification of antimicrobial resistance alleles.…”
Section: Introductionmentioning
confidence: 99%
“…As in Panama, the response included a parallel and sustained 12 months (24-month data are yet unpublished) decrease in the prevalence of scabies and impetigo (relative reduction of 94%, 95% CI 83-100 and 67%, 95% CI 52-83). 14 Finally, in a randomised controlled trial involving six communities in the Solomon Islands, coadministration of azithromycin with ivermectin led to similar decreases in the prevalence of scabies and impetigo compared with ivermectin alone; 15 however, a transient increase in the proportion of macrolide-resistant S aureus strains was reported after azithromycin mass drug administration.…”
Section: Control Of Scabies and Secondary Impetigo: Optimising Treatmmentioning
confidence: 98%